Evaluation Of The Impact Of Scanning Strategies On Residual Stresses In Selective Laser Melting - Mugwagwa, L.; Dimitrov, D.; Matope, S.; Yadroitsev, I. (The International Journal of Advanced Manufacturing Technology, 2019)
The occurrence of residual stresses in selective laser melting (SLM) presents challenges that limit the capability of the process to manufacture parts at industrial scale. These stresses can have irreversible effects such as warping and cracking of parts during and post manufacturing.One of the most important SLMparameters that should be controlled carefully in order to effectively manage residual stresses is the scanning strategy. This study presents an evaluation of four different scanning strategies, namely the island, successive, successive chessboard and least heat influence (LHI) scanning strategies with respect to their influence on residual stresses and distortions. All the scanning strategies were investigated by melting single tracks on tool steel substrates without powder. Measurement of residual stresses was performed on selected positions on the substrates before and after exposure to the laser beam using the x-ray diffraction technique. The successive chessboard scanning strategy was found to contribute to the least average residual stresses, and lowered residual stress by up to 40% relative to the default island scanning strategy. Further to this, the influence of the successive chessboard and island scanning strategies on distortions was evaluated. Similar to the residual stress findings, the successive chessboard contributed to lower form deviations compared to the island strategy. The scanning strategies were also evaluated based on their impact on total scanning times, with the successive chessboard strategy showing slightly lower scanning time than that for the island and LHI chessboard strategies.
Published Article
Keywords: Selective Laser Melting; Scanning Strategies; Residual Stresses; X-ray Diffraction